Cloning and functional analysis of a trypsin-like serine protease from Pinctada fucata martensii. Issue 126 (July 2022) - Liang, Haiying; Zhang, Meizhen; Shen, Chenghao; He, Junjun; Lu, Jinzhao; Guo, Zhijie
Abstract: Trypsin-like serine proteases (TLSs) play various roles in dietary protein digestion, hemolymph coagulation, antimicrobial peptide synthesis, and, in particular, the rapid immune pathways activated in response to pathogen detection. The cultured pearl industry, of which Pinctada fucata martensii is one of the most important species, is plagued by disease, thus leading to large economic losses. Herein, the molecular mechanisms underlying the innate immune response of P.f. martensii were explored . First, immune effector molecules from the P.f. martensii genome were screened and a TLS-like gene encoding a protein with a trypsin domain, herein designated as PmTLS, was identified. A multi-sequence alignment indicated a low sequence homology between PmTLS and other mollusk TLS-like proteins. Furthermore, a neighbor-joining phylogenetic analysis indicated that PmTLS has the closest genetic relationship to a Crassostrea gigas TLS. Additionally, real-time quantitative PCR (qPCR) analysis showed that PmTLS mRNA is constitutively expressed in all of the 6 examined P.f. martensii tissues, with significantly higher expression noted in hemocytes relative to the other tissues examined ( p < 0.05). P.f. martensii samples were then challenged with various pathogen-associated molecular patterns (PAMPs), including lipopolysaccharide, peptidoglycan, and polyinosinic acid. In the challenge groups, PmTLS was significantly upregulated in hemocytes at 48 h post-challenge when compared to the unchallenged controls. Furthermore, treatment with recombinant PmTLS (rPmTLS) also significantly inhibited the growth of most of the examined gram-negative bacteria tested in vitro ( p < 0.05), but it had little effect on the growth of the examined gram-positive bacteria. When examining morphological changes via transmission electron microscopy, rPmTLS treated bacteria exhibited morphological changes such as plasma wall separation. Thus, rPmTLS appears to play a bactericidal role by destroying bacterial cell membranes or cell walls, which subsequently leads to a release of the cellular contents and cell death. The findings presented herein have enabled further characterization of the immune defense mechanisms in P.f. martensii and may lead to improved disease control methods for the pearl cultivation industry. Highlights: A Trypsin-like serine proteases (TLS) was identified from Pinctada fucata martensii. The hemocytes is the main tissue for PmTLS expression and PmTLS was significantly up-regulated after PAMPs induction. rPmTLS showed antimicrobial activities against 4 kinds of Gram-negative bacteria. The mode of action of rPmKSPI on bacteria is the lysis of membrane type.